1971
DOI: 10.1103/physreva.4.1695
|View full text |Cite
|
Sign up to set email alerts
|

M-Subshell Fluorescence Yields and theL1L3Radiative Transition at

Abstract: High-resolution Ge(Li) and Si(Li) x-ray spectrometers and a wall-less anticoincidence multiwire proportional counter were used for coincidence measurements between various K and L x rays and M x rays of Np (Z = 93) and Cm (Z = 96) following 0' decay of Am 4 and Cf 4, respectively. The effect of multiple vacancies in the M shell was taken into account in the determination of the following mean M-subshell fluorescence yields: v~= 0.The close agreement of the various mean M-subshell fluorescence yields with that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Problems [13]. Karttunen et al [16] found [19] and further developed by Schiebl [20] (2) According to August [24] this expression, which is similar to that presented by Ruste [25], seems to reflect the physical situation better than other quantifications found in literature. This finding is also proved by the investigations of Sevov et al [4].…”
Section: Introductionmentioning
confidence: 52%
“…Problems [13]. Karttunen et al [16] found [19] and further developed by Schiebl [20] (2) According to August [24] this expression, which is similar to that presented by Ruste [25], seems to reflect the physical situation better than other quantifications found in literature. This finding is also proved by the investigations of Sevov et al [4].…”
Section: Introductionmentioning
confidence: 52%
“…The problem is to find a source which has resolvable x-ray lines below 5 keV and whose branching ratios are well known. Some work has been carried out on the Np M lines from 241Am source^.^,^,^^ However, the accepted M shell branching ratios for most of this work can be traced back to the early work of Karttunen et al, 12 which gave an absolute emission rate for the total M x-rays from 241Am as 0.0635 * 0.0060 per a decay and 0.470 f 0.045 M x-rays per La x-ray. In this section we consider in more detail the individual Np M lines which make up the total M lines from 241Am.…”
Section: Neptunium M Line Branching Ratiosmentioning
confidence: 99%